progress of sciences and knowledges - nan, nan (Iraqi Journal of Civil Engineering, 2008)
With the progress of sciences and knowledges, the development in the field of earth observation and measurements necessary ones, which helped in overcoming the problem of the time and cost required by field surveys in the division of agricultural land. In this study were recruited technical remote sensing, geographic information systems and field surveys for the purpose of assessing the accuracy of the division of agricultural land for agricultural area located in the eastern part of the Ramadi city as they were deducted from Google Earth. Comparison with the other conventional methods, the use of remote sensing and GIS gives adequate accuracy in the area of the division of agricultural land